Active with osteoArthritis (AktivA) – treatment of mild to moderate osteoarthritis in clinical physiotherapy practice - Inger Holm; May Arna Risberg (Fysioterapeuten, 2019)
Purpose: To evaluate the impact of AktivA on pain and physical function in patients with mild and moderate hip or knee osteoarthritis.